Balloon-occluded transarterial chemoembolization using a 1.8-French tip Coaxial microballoon catheter for hepatocellular carcinoma: Technical and safety considerations. Issue 2 (April 2014) - Matsumoto, Tomohiro; Endo, Jun; Hashida, Kazunobu; Ichikawa, Hitoshi; Kojima, Seiichiro; Takashimizu, Shinji; Watanabe, Norihito; Yamagami, Takuji; Hasebe, Terumitsu
Abstract: Objective : To evaluate the technical feasibility and safety considerations of balloon-occluded transarterial chemoembolization (B-TACE) using a newly developed 1.8-French (Fr) tip microballoon catheter for hepatocellular carcinoma (HCC).Material and methods : Between February 2013 and May 2013, 31 patients (20 males, 11 females; age range 56–85 years) underwent B-TACE using a 1.8-Fr tip microballoon catheter for unresectable HCC. The technical success rate, procedural complications, and adverse events of B-TACE were retrospectively investigated.Results : A total of 31 patients were subjected to 70 sessions of B-TACE using a 1.8-Fr tip microballoon catheter. The level of B-TACE was sub-subsegmental in 11, subsegmental in 35, segmental in 14, lobar in five, and right inferior phrenic artery in five sessions. The overall technical success rate was 99% (69 out of 70 sessions). As procedural complications, rupturing of the microballoon ( n = 3) and aneurysmal dilatation at the site of balloon occlusion ( n = 2) were encountered. There were no significant differences in any parameters between blood biochemical examination before and between two to four weeks after the procedure.Conclusion : A 1.8-Fr tip microballoon catheter enables selective catheterization in patients with HCC and B-TACE using the 1.8-Fr tip microballoon catheter is a safe procedure.